Beneficial Effects of Marine Algal Compounds in Cosmeceuticals - Thomas, Noel Vinay (MDPI, 2013)
The name “cosmeceuticals” is derived from “cosmetics and pharmaceuticals”, indicating that a specific product contains active ingredients. Marine algae have gained much importance in cosmeceutical product development due to their rich bioactive compounds. In the present review, marine algal compounds (phlorotannins, sulfated polysaccharides and tyrosinase inhibitors) have been discussed toward cosmeceutical application. In addition, atopic dermatitis and the possible role of matrix metalloproteinase (MMP) in skin-related diseases have been explored extensively for cosmeceutical products. The proper development of marine algae compounds will be helpful in cosmeceutical product development and in the development of the cosmeceutical industry.